A Review of the Role of Sphingosine-1-Phosphate in the Brain: An Important Mediator Implicated in the Central Nervous System - PUNSAWAD, Chuchard (Walailak Journal of Science and Technology (WJST), 2013)
Sphingosine-1-phosphate (S1P) is a bioactive lipid that signals through a family of G protein-coupled receptors, consisting of 5 members, termed S1P1, S1P2, S1P3, S1P4 and S1P5. Activation of S1P results in the regulation of several cellular functions, including cell proliferation, process retraction, cell survival and migration. Deregulation of S1P receptor expression and/or the S1P signaling pathway may play an important role in the development in the treatment of neurological disorders. The aim of the present review is to summarize the S1P signaling pathway and S1P receptor expression in the cellular components of human and rodent brains. The published information will be helpful to delineate the important mechanisms in the development of neurological disorders such as Alzheimer’s disease, multiple sclerosis, and traumatic brain injury, and serve as a guideline for the designing of further studies investigating S1P involvement in the brain. doi:10.14456/WJST.2014.17